FAKTOR-FAKTOR UTAMA KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR : ANALISIS LIKUIDITAS, PROFITABILITAS, DAN SOLVABILITAS - Agustin, Ella; Wijayanti, Anita; Masitoh, Endang (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
Sure Here’s the translation of the paraphrased paragraph into English: This study aims to examine and analyze the impact of liquidity, profitability, and solvency on financial performance. Secondary data was obtained from the financial statements of food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the period of 2021-2023. The research involved 26 companies using purposive sampling and employed multiple linear regression analysis. The findings indicate that profitability and solvency have a significant influence on financial performance, while liquidity does not show a significant effect.